Sub-Micron Two-Dimensional Displacement Sensor Based on a Multi-Core Fiber - Zhu, Kexin; Ren, Shijie; Li, Xiangdong; Liu, Yuanzhen; Li, Jiaxin; Zhang, Liqiang; Wang, Minghong (Photonics, 2024)
A sub-micron two-dimensional displacement sensor based on a segment of multi-core fiber is presented in this paper. Light at the wavelengths of 1520 nm, 1530 nm, and 1540 nm was introduced separately into three cores of a seven-core fiber (SCF). They were independently transmitted in their respective cores, and after being emitted from the other end of the SCF, they were irradiated onto the end-face of a single-mode fiber (SMF). The SMF received light at three different wavelengths, the power of which was related to the relative position between the SCF and the SMF. When the SMF moved within a two-dimensional plane, the direction of displacement could be determined based on the changes in power at different wavelengths. As a benefit of the high sensitivity of the spectrometer, the sensor could detect displacements at the sub-micron level. When the SMF was translated in 200 nm steps over a range from 5.2 μm to 6.2 μm, the sensitivities at the wavelengths of 1520 nm, 1530 nm, and 1540 nm were 0.34 dB/μm, 0.40 dB/μm, and 0.36 dB/μm, respectively. The two-dimensional displacement sensor proposed in this paper offers the advantages of high detection precision, simple structure, and ease of implementation.